STRUKTUR ORGANISASI DAN TATA ZONASI PERMUKIMAN ADAT DI DESA NGGELA, ENDE-FLORES - Fabiola T A Kerong (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment), 2016)
The Adat settlement of Nggela Village (Desa Nggela) is a traditional village in the Ende Regency of Flores Island, one of the Lesser Sunda Islands in the Indonesian archipelago. It is a vernacular settlement strictly regulated by layers of adat codes and practices, and governed by a unique organizational structure. The whole settlement is divided into several zones. These reflect three cultural dimensions. First, the historical journey the community has undertaken; second the cosmological beliefs of the people, third the environment within which the village is located. This article demonstrates how each of these elements has determined the spatial laying out of the village. The analysis of interrelationships suggests the emergence of values pertaining to beliefs; the function of the village as a living space for the whole community; and a container for various symbolic meanings. In so doing, the study demonstrates the more dominating and determining position of the adat advisory board members in governing day-to-day life of the settlement in comparison to the actual roles undertaken by members of the Desa Nggela’s adat leadership. Keywords: adat settlement; spatial zones; organizational structure; cosmological beliefs; topography, landscape Abstrak Permukiman adat Desa Nggela merupakan permukiman tradisional yang terletak di Kabupaten Ende di Pulau Flores, salah satu pulau di Kepulauan Sunda Kecil. Permukiman ini memberlakukan aturan adat secara ketat dan dikelola oleh struktur organisasi yang unik. Permukiman ini juga terdiri atas beberapa zona yang merefleksikan tiga dimensi budaya. Pertama, perjalanan sejarah dari komunitas yang telah dilewati; kedua, konsep kosmologi dari masyarakatnya; dan ketiga, lingkungan dimana permukiman ini berada. Tulisan ini memaparkan bagaimana setiap elemen budaya tersebut menentukan pola tata letak permukiman tersebut. Analisa dari hubungan antar elemen tersebut mengungkapkan kemunculan  dari nilai-nilai sistem kepercayaan; fungsi permukiman sebagai tempat hidup dari masyarakat Desa Nggela; dan kandungan nilai dari berbagai makna simbolik. Selain itu, paparan ini juga mengungkapkan dominasi dan posisi tetua adat dalam pengelolaan permukiman dibandingkan dengan peran pemimpin adat Desa Nggela.